TINGKAT KEKUMUHAN DAN PENANGANAN PADA PERMUKIMAN DESA BALE ATU KECAMATAN LUT TAWAR KABUPATEN ACEH TENGAH - Arie Julianda; Azmeri Azmeri; Eldina Fatimah (Prodi Magister Teknik Sipil Unsyiah, 2020)
Aceh Tengah District is one of the districts that have slum settlements. Based on the Decree of the Regent of Central Aceh No. 188.55 / 775 / DCKP / 2014, the determination of housing and slums in Central Aceh District includes 23 villages in 6 sub-districts, with a total area of 189.59 Ha. Bale Atu Village, located in Lut Tawar Subdistrict, is one of the very slum hamlets with a value of 4.22 and has a slum area of 0.56 Ha out of a total area of 2.5 Ha. Besides, Bale Atu Village is located in the center of Takengon City and a trade center as a strategic area, which must be immediately addressed so that slum areas do not expand. This study aims to evaluate the current level of a slum in the village of Bale Atu, and identify the current form of slum settlement. This research uses qualitative methods through observation and interviews and quantitative methods through a weighting system. Evaluation of the level of slum and handling is carried out based on the Technical Guidelines (Juknis) of the Regulation of the Minister of Public Works and Public Housing of the Republic of Indonesia (Permen PUPR RI) No. 02 / PRT / M / 2016. Evaluation of the level of slum includes aspects of slum conditions, aspects of land legality, and other aspects of consideration. The form of handling is based on the typology of slums and the physical handling of infrastructure. The results showed that the slum level of the settlements in Bale Atu Village was light slum with a total score of 23, and the slum level of all hamlets was a light slum where the total score of Dusun Barat was 31, Dusun Timur was 33, Dusun Utara was 29, and Dusun Selatan of 21. The form of slum settlement in Bale Atu Village is based on typology by handling hilly typology, and based on physical infrastructure, it is carried out through a restoration pattern. The handling of slum settlements in Bale Atu Village and all its hamlets is included in the 3rd priority scale of handling in Laut Tawar District.